Dari Pondok ke Platform Digital: Kreativitas Dakwah Gus Baha dalam Menjangkau Generasi Milenial dan Z - Istianah, Istianah; Kendy, Muhammad; Krisna Jaya, Canra (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2025)
The development of digital technology has transformed the way people access religious knowledge. Da'wah (Islamic preaching) is no longer confined to mosques or religious gatherings, but is rapidly expanding into digital spaces such as YouTube, TikTok, and Instagram. An interesting phenomenon in this context is the popularity of the preaching of Gus Baha, a traditional Islamic scholar from an Islamic boarding school (pesantren), who has become one of the most watched figures among Millennials and Generation Z. This study aims to analyze Gus Baha's creative preaching on digital platforms and how this style effectively reaches the younger generation. The research method used a descriptive qualitative approach through digital content analysis and observation of audience interactions. The results indicate that the strength of Gus Baha's preaching lies not in production technology, but in message creativity, storytelling, and authenticity, which fuel user-generated content and organic distribution on digital platforms. These findings demonstrate a